Single-Ring Intermediates Are Essential for Some Chaperonins - Bhatt, Jay M.; Enriquez, Adrian S.; Wang, Jinliang; Rojo, Humberto M.; Molugu, Sudheer K.; Hildenbrand, Zacariah L.; Bernal, Ricardo A. (Frontiers in Molecular Biosciences, 2018)
Chaperonins are macromolecular complexes found throughout all kingdoms of life that assist unfolded proteins reach a biologically active state. Historically, chaperonins have been classified into two groups based on sequence, subunit structure, and the requirement for a co-chaperonin. Here, we present a brief review of chaperonins that can form double- and single-ring conformational intermediates in their protein-folding catalytic pathway. To date, the bacteriophage encoded chaperonins φ-EL and OBP, human mitochondrial chaperonin and most recently, the bacterial groEL/ES systems, have been reported to form single-ring intermediates as part of their normal protein-folding activity. These double-ring chaperonins separate into single-ring intermediates that have the ability to independently fold a protein. We discuss the structural and functional features along with the biological relevance of single-ring intermediates in cellular protein folding. Of special interest are the φ-EL and OBP chaperonins which demonstrate features of both group I and II chaperonins in addition to their ability to function via single-ring intermediates.